Culture and Communication: Semiotics of the Venezuelan film comedy of the films Domingo de Resurrección (1982) y Papita Maní Tostón (2013) (Mayéutica Revista Científica de Humanidades y Artes, 2021)
This is a qualitative research supported by the hermeneutical method for the interpretation of the iconic signs and the semiotic codes of two Venezuelan humorous films. Among its purposes are to unveil semiotic codes, interpret iconic sentences and analyze communicational semiotics, considering the cultural features of Venezuelan society, through several scenes intentionally selected from Domingo de Resurrección and Papita Maní Tostón. The first film was made in the 1980s, when the decline of relative socioeconomic and democratic stability began in Venezuela, while the second was from 2013, when the country's political, moral and economic crisis was already aggravated. In both cinematographic works the characteristics of each period are evident, so the information collected was categorized according to the purposes and the emerging theory developed during the respective analysis. Among the most outstanding findings are the changes in markedly sexist behavior in the first film that are not seen in the second, violence as a phenomenon associated with the urban context, the decline of governmental institutions that is more evident in the second film, and the irruption of cultural codes associated with globalization that is imposed with new technologies.
Keywords: communication; Venezuelan comedy cinema; humor; semiotics; culture